Non-Hydrolytic Synthesis and Tribological Properties of Al2O3 Sol - Chen, Qiang; Zheng, Shaohua; Li, Wei; Song, Xiaoyun; Cao, Bingqiang (Asian Journal of Chemistry, 2012)
Oil-soluble Al2O3 sol was obtained via nonhydrolytic method. The aluminium trichloride was used as the precursors. Oleic acid and acetone was used as oxygen donor. The dispersion medium was lubricating oil. Al2O3 sol was characterized through X-ray diffraction analysis, UV-VIS spectrophotometer and scanning electron microscopy. Tribological properties of Al2O3 sol was studied through the four-ball friction test and thrust ring friction test. The results showed that the as-obtained Al2O3 nanoparticles in Al2O3 sol were dispersed very well with the size of about 80 nm and 20 # mechanical oil has a best lubricating effect with 14.74 % decreasing amplitude of friction coefficient and 9.86 % decreasing amplitude of wear scar diameter when Al2O3 sol was doped with 9 wt %.